ORGANIZATIONAL VERTICAL AND VIRTUAL INTEGRATION MODEL IN IMPLEMENTING LEAN MANUFACTURING TRANSFORMATION - A. P., Puvanasvaran (Penerbit UTeM, 2013)
It is a present-day instance of the recurring lean manufacturing theme in human history toward lean transformation. In order to achieve lean manufacturing, we therefore acquire a broader set of skills, creative and innovative approaches to analysis, using up-to-date tools and design through the implementation of lean manufacturing methodology and management transformation. Manufacturers and consumers that comprise the different status levels in the community will have easy and convenience access to the real-time oriented systems for lean manufacturing transformation. For this to occur, lean manufacturing transformation needs to be sufficiently integrated in the vertical and virtual in real-time lean process management. Therefore, the need for real-time lean simulation software is pointed out with special reference to lean manufacturing. The five sensory modalities applied to suite the real time lean process environment. The Organization Vertical and Virtual Integration model (OVVI) has parallels input values with other lean disciplines. In order to begin the process, this paper proposes both vertical and virtual integration into the development of real-time lean process management for enhancing problem solving capabilities.